The Correlation Fiber Intake, Obesity Status With Hypertension Patients Pressure At Tabanan III Health Center - Putu Della Ayu Wirayani; Lely Cintari; Ni Komang Wiardani (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
Hypertension is increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. Hypertension results in complications such as stroke, heart weakness, coronary heart disease, kidney disorders and others. The triggers for hypertension are distinguished from being non-controlled such as family history, gender, and age. Factors that can be controlled such as obesity, lack of physical activity, smoking behavior, consumption patterns of foods containing sodium and saturated fat. The purpose of this study is to analyze the relationship between fiber intake and obesity status with blood pressure of hypertensive patients in Tabanan III Health Center. This type of research was observational with a cross-sectional research design. The sample in this study was 41 people. Data collection uses identity forms, 24-hour recall method, weight and height measurements, and blood pressure measurements. Data was processed by statistical analysis of Spearman Rank Correlation. The results showed that 36 samples (87.8%) did not consume fiber as recommended, 17 samples (41.5%) were classified as obesity grade 1 and 30 samples (73.2%) grade I hypertension. There was no correlation between fiber intake and blood pressure. p value = 0.49 (p 0.05). There is no correlation between obesity status and blood pressure, p = 0.51 (p 0.05). Keywords: blood pressure level, fiber intake, obesity status, and hypertension